Insights into the olaparib-mediated cell death mechanisms in canine hematological malignancies: a different fate for CLBL-1 and GL-1 cell lines - Mucignat, Greta; Dejnaka, Ewa; Pauletto, Marianna; Lopparelli, Rosa Maria; Giantin, Mery; Pawlak, Aleksandra; Dacasto, Mauro (Frontiers in Veterinary Science, 2026)
IntroductionOlaparib (OLA) is a poly ADP-ribose polymerase inhibitor (PARPi) indicated for solid cancers harboring BRCA1/2 mutations. Recent evidences suggest that sensitivity to PARPis may also be influenced by other factors that impair the DNA repair mechanisms. Since various hematological malignancies exhibit these types of defects, this study aims to investigate further the mechanism of action of OLA in CLBL-1 and GL-1 canine cell lines, which showed different sensitivities to this PARPi.MethodsCLBL-1 and GL-1 cell lines were exposed to OLA (12.5, 25, and 50 μM) for 24 and 48 h and were subjected to preliminary cell death evaluations by flow cytometry. Then, both immunoblotting for the assessment of Bcl-2 and Bcl-XL, and RNA-seq were carried out after 24 h of exposure to OLA 25 and 50 μM. As for whole-transcriptome analysis, reads were pseudo-aligned (Kallisto) to the reference transcriptome, and differential gene expression (DGE) and functional analyses were performed with edgeR and clusterProfiler R packages.ResultsThe percentage of annexin V-positive cells after 24 h of incubation with OLA 50 μM was ~10%, increasing to ~40% in CLBL-1 cells and ~30% in GL-1 cells at 48 h. Bcl-2 and Bcl-XL expression increased after 24 h of incubation in CLBL-1 cells but decreased in GL-1 cells. DGE and functional analyses showed that, in CLBL-1 cells, the main processes affected by OLA were stress (e.g., ATF3, CEBPB) and apoptosis (e.g., BAX, BBC3). Conversely, in GL-1 cells, the regulation of tumor necrosis factor and interferon response-related terms, along with the upregulation of genes such as IL6, TNF, IFIT3, GSDME, and IL18, indicated the induction of pyroptosis.DiscussionThe comprehensive transcriptomic analysis helped clarify the distinct mechanisms of OLA-induced cell death in CLBL-1 and GL-1 cells, which showed different sensitivities to OLA. Indeed, this PARPi appeared to interact with immune checkpoints, stress sensors, and interfere with cell proliferation, leading to various types of cell death. As canine lymphoma is a significant concern in veterinary oncology and a valuable model for its human counterpart, this study further confirms the potential of PARPi as a therapeutic approach in hematological malignancies in both species.